Determinantes do envelhecimento populacional nos municípios goianos: perspectivas socioeconômicas e de qualidade de vida - Rodrigues, Leandro Pinho (2025)
Studies indicate that the world's population is aging at an increasing rate. Successive declines in birth and death rates, combined with improvements in quality of life, urban infrastructure, and access to health care, have contributed to an increase in life expectancy. Although these additional years of life represent an important social advance, they also pose new challenges for public administrators, especially in planning policies aimed at the elderly population. In this scenario, this research initially aims to outline the demographic profile of the state of Goiás and then analyze how the birth rate, socioeconomic factors (such as income, education, health, among others), morbidity and mortality factors, and quality of life indicators influence population aging in the state of Goiás. As part of the Public Policy research line, this dissertation seeks to contribute to the formulation and implementation of more effective actions aimed at the population aged 60 or over. The relevance of the study lies in the analysis of the demographic profile of the elderly population of Goiás, offering support for more precise action by the government. The methodology was structured in two stages: the first consisted of using descriptive statistics to organize and present the data; the second applied multiple linear regression techniques, using the Ordinary Least Squares (OLS) method, with the aim of identifying the quality of life factors and socioeconomic conditions that most impact aging in the municipalities of Goiás. The construction of the Population Aging Index (IEP) allowed us to gather relevant information about the demographic dynamics of the state. The econometric results suggest that the main cause of population aging in Goiás is the reduction in the birth rate, although socioeconomic factors also have an influence, albeit to a lesser extent. Thus, the findings of this research can assist public managers in developing evidence-based policies, in addition to strengthening the debate on population aging and its social implications.